2018
DOI: 10.1177/2325967118785169
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From Conservative Treatment of Shoulder Idiopathic Adhesive Capsulitis and Factors Associated With Developing Contralateral Disease

Abstract: Background:Idiopathic adhesive capsulitis is a common condition resulting in painful multidirectional restriction of motion without other identifiable shoulder abnormality. First-line therapies for this condition are nonoperative, but limited data are available regarding which treatments are most effective. Factors associated with contralateral disease are not well established.Hypothesis:Younger patients will have a better response to treatments, and older patients and patients with diabetes will be more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Prior studies have shown ADHESIVE CAPSULITIS TREATMENT e37 efficacy in physical therapy, as well as corticosteroid injections in the treatment of adhesive capsulitis, although little data exist on the ideal number of corticosteroid injections. 6,13 One of the interesting demographic findings from this study was the higher percentage of men with diabetes (24.8% vs 17.3% [P ¼ .001]), and a higher percentage of women with hypothyroidism (13.4% vs 5.6% [P ¼ .001]) presenting with adhesive capsulitis. Prior studies have shown a higher prevalence of hypothyroidism among women in the general population, with a prevalence of approximately 8% in women compared with just 1% in men, but the percentages of patients with adhesive capsulitis and hypothyroidism far exceeded this for both sexes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Prior studies have shown ADHESIVE CAPSULITIS TREATMENT e37 efficacy in physical therapy, as well as corticosteroid injections in the treatment of adhesive capsulitis, although little data exist on the ideal number of corticosteroid injections. 6,13 One of the interesting demographic findings from this study was the higher percentage of men with diabetes (24.8% vs 17.3% [P ¼ .001]), and a higher percentage of women with hypothyroidism (13.4% vs 5.6% [P ¼ .001]) presenting with adhesive capsulitis. Prior studies have shown a higher prevalence of hypothyroidism among women in the general population, with a prevalence of approximately 8% in women compared with just 1% in men, but the percentages of patients with adhesive capsulitis and hypothyroidism far exceeded this for both sexes.…”
Section: Discussionmentioning
confidence: 75%
“…4,5 Once the diagnosis of adhesive capsulitis is correctly made (which can be difficult at times), initial treatment commonly involves a course of physical therapy (PT) focusing on gentle, progressive stretching with or without a glenohumeral corticosteroid injection. 6 Supplemental treatments to physical therapy are numerous and include corticosteroid injections, antiinflammatory medications, hydrodilation, and capsular release with manipulation under anesthesia. Intraarticular corticosteroid injections have been shown to be effective in treating adhesive capsulitis, with improvements in pain and range of motion (ROM), whereas treatment with oral antiinflammatory medications has not generally produced effective results.…”
mentioning
confidence: 99%
“…It remains uncertain, however, whether there is an appropriate placement or misplacement of injected treatment agents at the MTrPs [35]. Thus, a blind technique would cause residual or earlier recurrence of symptoms [36]. To resolve this, US-guided injections of treatment agents have been attempted, whose accuracy has been well described in the literature [37].…”
Section: Efficacy Outcomesmentioning
confidence: 99%
“…Actualmente su prevalencia real se desconoce, pero se estima que se presenta en 5.3% de la población 1 en el rango de 40 a 65 años de edad, 5 afecta al género femenino en 70% de los casos 1 y hasta en 20% de la población con diabetes, en particular en la extremidad no dominante se manifiesta entre 40 y 50% de los casos de forma bilateral, 1 condición que afecta sobre todo a la población diabética y a los que muestran el primer cuadro antes de los 50 años. 5 Es una patología autolimitada, con una duración entre 1 y 3.5 años, con un promedio de 30.5 meses. El diagnóstico diferencial debe realizarse con lesiones del manguito de los rotadores, tendinitis o bursitis calcificada o con un proceso degenerativo glenohumeral.…”
Section: Introductionunclassified